Comparative Study of Elementary School Students’ Understanding of Geometry Concepts through Ethnomathematics and Conventional Approaches - Isneli Yulailah; Rika Mulyati Mustika Sari; Rafiq Zulkarnaen; Indrie Noor Aini (PRISMA, 2026)
This study aims to investigate and compare differences in elementary school students’ understanding of geometric concepts between those who experienced ethnomathematics-based learning and those who received conventional instruction. This study employed an ex post facto comparative design involving 54 fifth-grade students divided into two groups. Data were collected using a geometry concept understanding test that met validity (0.92) and reliability (Cronbach’s Alpha = 0.86) criteria. The data were analyzed using descriptive and inferential statistics. The results showed that the mean score of the ethnomathematics group (M = 83.96; SD = 4.74) was higher than that of the conventional group (M = 71.15; SD = 2.58). Welch’s t-test indicated a statistically significant difference between the two groups (t = 12.33; df = 40.17; p < 0.001). These findings indicate that ethnomathematics-based learning is associated with higher levels of students’ understanding of geometric concepts compared to conventional instruction. However, due to the ex post facto design, the findings should be interpreted as associative rather than causal.